Pengaruh Operating Capacity, Sales Growth, Arus Kas dan Leverage Terhadap Financial Distress - Siti Noviati Uswatun Khasanah; Fatmasari Sukesti; Nurcahyono Nurcahyono (UMSurabaya Publishing, 2021)
This research was conducted the empirically prove the factors that influence Financial Distress by using the variables operating capacity, sales growth, cash flow, and leverage in transportation companies listed on the Indonesia Stock Exchange in 2015–2020. This type of research is quantitative research with sampling technique using purposive sampling method, namely the selection of samples with criteria determined by the researcher. The method used in this study uses multiple linear regression with the help of the SPSS version 25 program. The results in this study indicate that operating capacity has a positive effect on financial distress, which means that a low operating capacity value will cause financial distress. Sales growth and cash flow do not effect financial distress, which means the size of the value of sales growth and cash flow does not affect the occurrence of financial distress. Leverage has a positive effect on financial distress, which means that the high value of debt will cause financial distress.